Demand for Cigarettes and Optimal Tax in Malaysia - Mohamed Nor, Norashidah (2011)
Tobacco use is the leading cause of several preventable disease and premature death in the world today. It is estimated more than 14,000 people die every day and if current trend continues; more than 8 million people will die by 2030. 80% of these premature deaths are happening in developing countries In this study, the elasticities of demand for cigarette are empirically examined using the three demand models; conventional demand model, myopic demand model and rational addiction demand model. In general, the estimated coefficient of price elasticity of demand for cigarette from the three models was found to be less than 1 or inelastic. Price is a highly significant determinant of demand for cigarette in the long run but the demand for cigarette is independent of price in the short run. The finding suggested that cigarette is an addictive good since past consumption of cigarette has a positive impact on the current consumption. The addiction of cigarette among Malaysian smokers is due to their myopic behavior in accord with the myopic addiction hypothesis, where only past consumption is considered but future consumption is ignored when making current consumption. This study also found that income per capita and the number of youth population have a positive relationship with the consumption per capita but only significant in the short run. The positive coefficient of income elasticity of demand indicated that cigarette is a normal good. However, the short run coefficient of income elasticity of demand is greater than 1 which suggested that cigarette is in the category of luxury good. Therefore, any positive shock on income in the short run will increase consumption more than proportionate. Excise tax rate was found to be an effective measure by the government to reduce consumption for cigarette. However, since demand for cigarette is inelastic, increasing excise tax rate also meant additional tax revenue to the government. The analysis onoptimal cigarette tax was derived using Laffer Curve formula and this led us to conclude that there are ample opportunities for government to increase current excise tax rate before reaching the optimal level. On the other hand, reducing cigarette consumption via government campaigns in mass media was found to be ineffective. Behavioral change takes a longer time and to realize the objectives of the campaign, government should conduct on-going campaign activities to deter smoking among the population.